2006
DOI: 10.1111/j.1365-2966.2006.10159.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-outburst phase of McNeil's nebula (V1647 Orionis)

Abstract: We present a detailed study of the post-outburst phase of McNeil's nebula (V1647 Orionis) using optical B, V, R, I and near-infrared (NIR) J, H, K photometric and low-resolution optical spectroscopic observations. The observations were carried out with the Himalaya Faint Object Spectrograph Camera (HFOSC), NIR camera (NIRCAM), the Tata Institute of Fundamental Research (TIFR) Near-Infrared Camera (TIRCAM) and NICMOS cameras on the 2-m Himalayan Chandra Telescope (HCT) and 1.2-m Physical Research Laboratory (PR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 27 publications
(60 reference statements)
5
27
2
Order By: Relevance
“…Since OI λ7773Å cannot be formed in photosphere of cool stars, the absorption component is due to warm gas in the envelope or hot photosphere above disc, while the emission component might be due to the hot gas region from which Hα is also being emitted. Ojha et al (2006) reported a decreasing trend in the W λ of OI λ7773Å from the beginning till end of the 2003 outburst which was interpreted to be possible decrease in turbulence in outer envelope during the outburst period. Ojha et al (2006), in contrast to the increase of W λ of other lines, could be due to increase in the W λ of OI λ7773Å emission component.…”
Section: Oxygen Linesmentioning
confidence: 99%
See 4 more Smart Citations
“…Since OI λ7773Å cannot be formed in photosphere of cool stars, the absorption component is due to warm gas in the envelope or hot photosphere above disc, while the emission component might be due to the hot gas region from which Hα is also being emitted. Ojha et al (2006) reported a decreasing trend in the W λ of OI λ7773Å from the beginning till end of the 2003 outburst which was interpreted to be possible decrease in turbulence in outer envelope during the outburst period. Ojha et al (2006), in contrast to the increase of W λ of other lines, could be due to increase in the W λ of OI λ7773Å emission component.…”
Section: Oxygen Linesmentioning
confidence: 99%
“…Ojha et al (2006) reported a decreasing trend in the W λ of OI λ7773Å from the beginning till end of the 2003 outburst which was interpreted to be possible decrease in turbulence in outer envelope during the outburst period. Ojha et al (2006), in contrast to the increase of W λ of other lines, could be due to increase in the W λ of OI λ7773Å emission component. …”
Section: Oxygen Linesmentioning
confidence: 99%
See 3 more Smart Citations